Mini-review: Functions and Action Mechanisms of PQQ in Osteoporosis and Neuro Injury - Wen, Hao; He, Yuan; Zhang, Ke; Yang, Xiaobin; Hao, Dingjun; Jiang, Yonghong; He, Baorong (Current Stem Cell Research & Therapy, 2020)
Pyrroloquinoline Quinone (PQQ) is the third coenzyme found after niacinamide and flavone nucleotides and is widely present in microorganisms, plants, animals, and humans. PQQ can stimulate the growth of organisms and is very important for the growth, development and reproduction of animals. Owing to the inherent properties of PQQ as an antioxidant and redox modulator in various systems. In recent years, the role of PQQ in the field of osteoporosis and neuro injury has become a research hotspot. This article mainly discusses the derivatives, distribution of PQQ, in vitro models of osteoporosis and neuro injury, and the research progress of its mechanism of action. It provides new ideas in the study of osteoporosis and neuro injury.
Keywords: homologous proteins